2009
DOI: 10.3922/j.psns.2009.2.014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of negative emotions in high trait anxious individuals: An ERP study.

Abstract: Literature has shown that failures in the ability to down-regulate negative emotions are the core substrate of anxiety disorders. Previous studies have investigated this issue by encouraging individuals to voluntarily change how they think about a situation in order to decrease its emotional impact. The majority of studies has demonstrated that explicit instructions to reduce negative affect in anxious individuals are usually ineffective. Thus, the goal of the present study was to investigate whether an implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 48 publications
2
37
0
Order By: Relevance
“…Evidence shows that the use of cognitive strategies to regulate emotions, such as attention allocation, can be undermined by high levels of anxiety (Berggren & Derakshan, 2013;Mocaiber et al, 2009;Sheppes, Luria, Fukuda, & Gross, 2013), in line with results showing that affective states may be as important as cognitive skills for the regulation of emotions (Kanske & Kotz, 2012).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Evidence shows that the use of cognitive strategies to regulate emotions, such as attention allocation, can be undermined by high levels of anxiety (Berggren & Derakshan, 2013;Mocaiber et al, 2009;Sheppes, Luria, Fukuda, & Gross, 2013), in line with results showing that affective states may be as important as cognitive skills for the regulation of emotions (Kanske & Kotz, 2012).…”
mentioning
confidence: 58%
“…Finally, our findings contribute to the discussions regarding the mechanisms that underlie and foster emotion regulation skills (Bishop, 2007;Derryberry & Reed, 2002;Kanske & Kotz, 2012;Mocaiber et al, 2009;Oliveira et al, 2013;Sheppes et al, 2013), and support the proposition that meditation may be a valuable strategy for the study of regulatory processes (Menezes, Pereira, & Bizarro, 2012). However, our results should be extended and complemented by larger scale trials, as well as by the usage of more ecologically valid measures.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[36] Moreover, a number of neuroscientific studies have employed scales to detect anxiety levels and have associated the scores obtained with hormonal, behavioral, neurophysiological and cardiac parameters. [13,32] Mocaiber and colleagues (2009) showed that HTA individuals are susceptible to modifications in affective contexts. Participants (LTA and HTA individuals) performed an attention task (bar orientation discrimination) while emotional distractive pictures (mutilated bodies) were presented.…”
Section: Discussionmentioning
confidence: 99%
“…TA has been also considered as an important predictor of cardiovascular disease. [13] In a previous study of our group, [14] the putative role of basal HRV as predictor of anxiety and affect levels was tested by means of wavelet transform tools in a non-clinical population of undergraduate students. Anxiety level (trait anxiety) was evaluated through Spielberg's State and Trait Anxiety Inventory (STAI-T) [15,16] and positive and negative affect scores were measured through the Positive (PA) and Negative (NA) Affect Schedule (PANAS).…”
Section: Figurementioning
confidence: 99%